Reply to O'Brien et al. (1st June 2014) - Stanford, Dennis; Bradley, Bruce
Abstract : Across Atlantic ice (AAI) sets out specifically to propose an alternative hypothesis of early human entry into the Americas and to stimulate research (Stanford & Bradley 2012: 16). O'Brien et al .'s response (above) primarily contains an unsupported dismissal of the evidence and these ideas. Unfortunately, to date, no work equivalent to AAI has been presented for any other Clovis origin hypothesis; this would be most welcome, especially from those who critique and reject the Solutrean hypothesis with unsupported assertions. For convenience we respond to each of O'Brien et al.'s critiques in the order in which they appear.